Anti-hypercholesterolemic activity of herbal juice with shelf life of 50 and 100 days in male rats induced by PTU and high-fat diet - Sari Meisyayati; Ade Arinia Rasyad; Frelis Setya Nanda; Ayu Lestari; Alex Ferianto; Rizki Wahyudi (Universitas Islam Indonesia, 2022)
AbstractBackground: Herbal juice with the composition of rosella flower, garlic, red ginger, dan lime extract, apple cider vinegar andhoney has been proven to be effective as an anti-hypercholesterolemia and has a high level of safety through acute and sub chronic toxicity tests that have been carried out. To be marketed, it is also necessary to know how long this herbal juice formula preserve its antihyperlipidemic effect during the storage process.Objective: This study was aimed to examine the effectiveness of herbal juice stored for 50 days and 100 days in PTU-induced rats and high-fat diet.Methods: This test used 6 groups of animals consists of group I (Na CMC 0.5%/negative control), group II (fresh herbal juice), group III (herbal juice stored 50 days at room temperature), group IV (herbal juice stored for 50 days at cold temperatures), group V (herbal juice stored for 100 days at room temperature), and group VI (herbal juice stored for 100 days at cold temperatures). The dosage of the test preparation was 5.4 ml/kg given once a day for 10 days. Induction was carried out using PTU ad libitum and high-fat diet twice a day for 10 days. Measurement of serum total cholesterol levels was carried out on day 0 and 11 using the CHOD-PAP method.Results: Groups II and IV could reduce cholesterol significantly compared to the negative control group (p<0.05), while the other groups could increase blood cholesterol level.Conclusion: Herbal juice showed effectiveness as anti-hypercholesterolemia in male white rats after being stored for 50 days and 100 days. Shelf life and temperature do not reduce its activity.Keywords:anti-hypercholesterolemia, herbal juice, shelf life, temperatureIntisariLatar belakang:Jus herbal dengan komposisi sari bunga rosella, bawang putih, jahe merah, jeruk nipis, cuka apel dan madu telah terbukti efektif sebagai antihiperkolestrolemia dan memiliki tingkat keamanan yang tinggi melalui uji toksisitas akut dan subkronik yang telah dilakukan. Untuk dapat dipasarkan, perlu pula diketahui seberapa lama formula jus herbal ini mampu mempertahankan efek antihiperlipidemianya selama proses penyimpanan.Tujuan:Penelitian ini bertujuan untuk mengkaji efektivitas jus herbal yang disimpan 50 hari dan 100 hari pada tikus yang diinduksi PTU dan pakan tinggi lemak.Metode:Pengujian ini menggunakan 6 kelompok hewan perlakuan yang terdiri dari kelompok I (NaCMC 0,5%/kontrol negatif), kelompok II (jus herbal segar), kelompok III (jus herbal yang disimpan 50 hari suhu kamar), kelompok IV (jus herbal yang disimpan 50 hari suhu dingin), kelompok V (jus herbal yang disimpan 100 hari suhu kamar), dan kelompok VI (jus herbal yang disimpan 100 hari suhu dingin). Dosis sediaan uji 5,4 ml/kgbb yang diberikan satu kali sehari selama 10 hari. Induksi dilakukan dengan pemberian PTU ad libitum dan pakan tinggi lemak 2x sehari selama 10 hari. Pengukuran kadar kolesterol total serum dilakukan pada hari ke-0 dan ke-11 dengan metode CHOD-PAP.Hasil:Kelompok II dan IV dapat menurunkan kolesterol secara signifikan dibandingkan kelompok kontrol negatif (p<0,05), sementara kelompok lain mengalami peningkatan kadar kolesterol darah.Kesimpulan: Jus herbal menunjukkan efektivitas sebagai antihiperkolesterolemia pada tikus putih jantan setelah disimpan selama 50 hari dan 100 hari. Masa simpan dan suhu tidak mengurangi aktivitasnya.Kata kunci :antihiperkolesterolemia, jus herbal, masa simpan, suhu